Development of enterprise investment activity - Lin Chen (Харківський національний автомобільно-дорожній університет, 2024)
In the diploma work, the concept of "investment activity" has been improved, which, in contrast to the existing ones, characterizes it as a set of actions of the enterprise to achieve the goals of its development. The methodological approach to assessing the effectiveness of investments in the development of the enterprise, which, unlike the existing ones, is based on the calculation of the target indicator of the development of the enterprise, which determines the optimal direction of investment, has been improved. An investment project for the renewal of production equipment has been proposed and substantiated. Forecast assumptions regarding the development of the object of study are the sustainable development of the enterprise and its investment activity.
Keywords: investment activity; investment project; enterprise development; net present value; scenario analysis